On a Coupled System of Fractional Differential Equations via the Generalized Proportional Fractional Derivatives. (14th July 2022) - Abbas, M. I.; Ghaderi, M.; Rezapour, Sh.; Thabet, S. T. M.
Abstract : This work investigates the existence and uniqueness of solutions for a coupled system of fractional differential equations with three-point generalized fractional integral boundary conditions within generalized proportional fractional derivatives of the Riemann-Liouville type. By using the Schauder and Banach fixed point theorems, we study the existence and uniqueness of solutions for the aforesaid system. Finally, we present an example to validate our theoretical outcomes.